Physico-Chemical and Microbiological Composition of Kradi Cheese - Punoo, Hilal Ahmad (Indian Journal of Dairy Science, 2018)
Kradi cheese is a semisoft cheese of Jammu and Kashmir State India with no information about the product composition or characteristics. The aim of the present study was to analyze kradi cheese marketed in Shopian, Pahalgam, Rajouri and Poonch areas of Jammu and Kashmir for its physico-chemical and microbiological characteristics. All the samples were brought to Dairy Technology Division National Dairy Research Institute Karnal India in insulated containers within twenty four hours from producers. The samples were analysed for fat, protein, moisture, ash, lactose content, acidity and fat leakage. Coliform count, total viable count and yeast and mould count were analyzed for studying microbiological characteristics. The following range of variability was observed for each parameter: fat 6.35-28.63, protein 20.96-32.37, moisture 44.91-59.01, ash 1.26-1.66, lactose 0.61-1.37, pH 5.04 to 5.41, acidity 0.51 -.57, fat leakage 2.21-3.01, coliform 3.92-4.38 log cfu/g, total viable count 4.96-5.25 log cfu/g, yeast and mould 3.84-4.22 log cfu/g. The analysis of variance revealed significant (pâ‰¤0.01) differences between samples for all four market areas for physico-chemical and microbiological characteristics. The results show high variation among samples proving that there has not been a standard production procedure. A large number of studies need to be carried out for this kind of traditional food items.